Alchemical Myths and Hermetic Representations in the Feminine Imaginary of Salt - Flores Fernández, María (Amaltea. Journal of Myth Criticism, 2021)
Drawing from the Imaginary Studies through the prism of “mythodology”, introduced by Gilbert Durand in Figures mythiques et visages de l’œuvre (1979), this article addresses the female transmutation of the environment as an allegory, where salt and water have been associated throughout history to the female body. Therefore, the current study aims to elucidate how landscape and women are comparable in the junction of spatial, mythological and socio-cultural elements which, from a symbolic point of view, nowadays contribute to the definition of the woman-water archetype in a hermetic dimension of the saline landscape.